Digital real psycho-semioitic language uses of global and regional \"Feeling of fear and some requested rol models in the future through virtual reality created in the real universe - ALGÜL, NEVİN (My University, 2022)
The subject of this article is: First of all, after examining whether "FEAR FEELING" is dominant in managing and guiding people; To reveal what linguistic and visual indicators can be that fuel, emphasize and adjust the dose of this feeling in order to manage, direct and guide large masses of people in the desired direction, and the new world that pierces the global local digital real psycho-semiotic language uses and some of them through these linguistic and visual indicators. It is to present some of the role models that are contrary to the established order, which I define as the indicators of the order of the future, but that are desired in the future
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Fear; Linguistic; Visual; Indicative; Psycho-Semiotic Language Uses; Managing; Motivating; Large Masses of People; Anti-establishment Role Model.